Influence of radiation-induced defects on the overheating of a metal target; 6th International Congress on Energy Fluxes and Radiation Effects; 20th International Symposium on High-Current Electronics (20SHCE), Tomsk, September 16-22 - Egorova Yu. I. Yulia Ivanovna; Prima A. I. Artem Igorevich; Zhu X. P.; Ding L.; Zhang Q.; Pushkarev A. I. Aleksandr Ivanovich; Lei M. K. Ming Kai (2018, 2018)
Title screen